PERUBAHAN MUTU FISIK CABAI MERAH KERITING (Capsicum annuum L.) MENGGUNAKAN BERBAGAI JENIS KEMASAN PLASTIK PADA PENYIMPANAN SUHU RENDAH - Kusmali, Muh.; Gumaran, Setyadi; Harmiansyah, Harmiansyah; Fil’aini, Raizummi; Utari, Ni Wayan; Dermawan, Muhammad; Bossa Samang, Andi Marlisa (Fakultas Pertanian, Universitas Janabadra, 2024)
Curly red chilies are a horticultural crop product that has high economic value but is easily damaged. Storage temperature conditions and exposure to oxygen can influence the rate of decline in the quality of curly red chilies, so determining the type of packaging with optimum permeability according to the needs of red chili metabolic activity is very important to pay attention to. This research aims to analyze the effect of plastic packaging type in inhibiting the rate of decline in the quality of curly red chilies in low temperature storage. The research method used a Completely Randomized Design (CRD) with a single factor, namely the treatment of the type of plastic packaging (P), which consisted of 6 levels of treatment, namely Polypropylene (PP), Polyethylene (PE), High Density Polyethylene (HDPE), Low Density Polyethylene (LDPE), Wrapping and Control. Each treatment unit was carried out 3 times. The quality parameters observed were changes in water content, weight loss, damage, hardness and color with measurement intervals every 2 days during storage. The results of the research showed that the treatment of the type of plastic packaging at low temperature storage had a significant effect on the water content, weight loss, damage, hardness and color of curly red chilies during storage. The Polypropylene plastic packaging treatment was better able to maintain the quality of curly red chilies until day-16 with a water content of 79.98%, the lowest weight loss of 9.67%, the lowest damage of 36.19%, hardness of 9.59 N, the highest color index L* (brightness) of 31.77 and a * (reddish) high 35.46.